Pengembangan Video Tutorial Berbasis Web Untuk Pembelajaran Keterampilan Mencuci Pakaian Peserta Didik Tunagrahita - Teguh Denada Diah Ayu Ningtyas; Budiyanto Budiyanto; Asri Wijiastuti (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
The development of web-based tutorial videos for learning laundry skills for students with disabilities aims to develop web-based tutorial videos for learning laundry skills for students with disabilities. This study uses Research and Development (R&D) with the ADDIE (Analyze, Design, Develop, Implement, Evaluate) model. The development process consists of needs analysis, design, and development of media that are piloted to students. Data collection was carried out through questionnaires and data analysis using percentages. The results of the study show that: (1) video tutorials have been successfully developed for learning web-based laundry skills in students with disabilities, (2) expert validation shows that this media is very feasible to use with a score of 84% from media experts, 98% from material experts, and 86% by practitioners (3) the results of field trials show the effectiveness of web-based video tutorial media in improving the washing skills of students with disabilities, with a value of Z = -2.549 and p = 0.11.